Outcomes of preterm infants discharged early from a South African Kangaroo Mother Care Unit - Williams, Sadeeka (Department of Paediatrics and Child Health, 2020)
Background: Over 15 million preterm babies are born annually and are the leading contributor to neonatal deaths. Kangaroo Mother Care (KMC), incorporating skin-to-skin care, breastfeeding, early discharge and close follow up, decreases morbidity and mortality in preterm and low-birth-weight infants. Few recent South African studies have looked at outcomes of KMC beyond the neonatal period. Aim: The primary objective was to describe the post-discharge clinical course of KMC infants over six months. The secondary objectives were to correlate neonatal and maternal characteristics pre-discharge to outcomes – mortality and morbidity. Setting: George Hospital is the regional hospital for the Eden and Central Karoo districts, with its tertiary referral centre 400km away in Cape Town. In these areas, poverty and teenage pregnancies result in more than a quarter of learners dropping out of school before completing Grade 12. The hospital has intensive care, high care and KMC units. Methods: This was a retrospective descriptive study which reviewed folders of neonates discharged from KMC in 2013. Neonates with birth weights of 2000g or more and neonates referred out were excluded. Hospital readmissions were used as a proxy for morbidity and a descriptive analysis was done. Results: Fifty-two infant records were reviewed. Thirteen infants (25%) accounted for 21 readmissions. Six readmissions occurred in winter. There were significant associations between being readmitted and birth weight and breastfeeding. Thirty-five of the 52 infants were alive at six months. None were known to have died. Conclusion: Larger prospective studies on KMC infant outcomes are needed in South Africa